Great wedding - Evans, Max (Univ. N.M. Press Albuquerque, NM, 1963)
This novella, an unabashed sequel to the The Rounders, Dusty and Wrangler and Old Fooler have more adventures and still can't escape the clutches of rancher, Jim Ed Love. There are moments in the story, written in Taos, the presage the literary life Max would later lead.
53432
Keywords: Cowboys -- New Mexico; New Mexico